Characterisation of lung cell infiltration during the early stage of infection by porcine reproductive and respiratory syndrome virus type 1 strains of different virulence - Karola Fristiková; José María Sánchez-Carvajal; Carmen Álvarez-Delgado; Fernanda Larenas-Muñoz; Macarena Rodríguez-Ruiz; Inés Ruedas-Torres; Inmaculada Barranco; Francisco Javier Salguero; Francisco José Pallarés; Enric Mateu; Librado Carrasco; Irene Magdalena Rodríguez-Gómez; et al. (Veterinary Microbiology, 2025)

The spread of Aoroides longimerus Ren & Zheng, 1996 across the Mediterranean and the Atlantic: genetic diversity, anthropogenic transport, and ecological implications - JOSÉ MANUEL GUERRA-GARCÍA; ANDREA DESIDERATO; SERENA MUCCIOLO; CARLOS NAVARRO-BARRANCO; MACARENA ROS; JASMINE FERRARIO; PAULA MORETTI; AGNESE MARCHINI; NAWFEL MOSBAHI; SOFÍA RUIZ-VELASCO; IGNACIO GESTOSO; PATRÍCIO RAMALHOSA; et al. (Mediterranean Marine Science, 2025)
Accurate knowledge of the global distribution of non-indigenous species (NIS) is essential for understanding their invasion dynamics and for implementing timely management measures. This study reports the first records of the marine amphipod Aoroides longimerus, putatively native to the East Asian coast, in Italy (2018), Spain (2019) and Tunisia (2022) and provides the earliest documented record of the species in its introduced European range (Portugal, 2011). Furthermore, it expands the species’ known distribution in mainland Portugal (including the northernmost record), Macaronesia (with first records in the Canary Islands and Madeira), and confirms its presence along the Atlantic coasts of France and the Netherlands. Aquaculture facilities, particularly those associated with oyster farming, are probably the primary vector of introduction, while recreational boating may have contributed significantly to secondary dispersal. In comparison to other exotic amphipods, A. longimerus remains absent from many marinas, ports and/or aquaculture facilities in the Mediterranean Sea and adjacent regions, such as the Red Sea. This suggests that the species may still be in the early stages of expansion, or that its dispersal ability across marinas and ports is more limited than that of other amphipods. The present study, however, highlights several key ecological traits of A. longimerus: (i) it can survive year-round despite seasonal fluctuations, and reach high local densities, (ii) it exhibits strong colonisation capacity, as shown by its rapid establishment on settlement plates, and (iii) it displays opportunistic feeding behaviour, primarily consuming detritus. These characteristics underscore the importance of continuous surveillance and effective communication with stakeholders to prevent further expansion of this species.

Discovering potential biomarkers for Ochratoxin A production by Penicillium nordicum in dry-cured meat matrices through untargeted metabolomics - David Garrido-Rodríguez; María J. Andrade; Josué Delgado; Eva Cebrián; Inmaculada Barranco-Chamorro (Food Control, 2024)

Kinetics of the expression of CD163 and CD107a in the lung and tonsil of pigs after infection with PRRSV-1 strains of different virulence - Jose M. Sánchez-Carvajal; Irene M. Rodríguez-Gómez; Librado Carrasco; Inmaculada Barranco; Belén Álvarez; Javier Domínguez; Francisco J. Salguero; Jaime Gómez-Laguna (Veterinary Research Communications, 2019)